2004
DOI: 10.1002/ajpa.20035
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and infant head circumference sexual dimorphism in primates

Abstract: Studies have shown that after controlling for the effects of body size on brain size, the brains of adult humans, rhesus monkeys, and chimpanzees differ in relative size, where males have a greater volume of cerebral tissue than females. We assess whether head circumference sexual dimorphism is present during early development by evaluating sex differences in relative head circumference in living fetuses and infants within the first year of life. Head circumference is used as a proxy for brain size in the fetu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 49 publications
4
18
0
Order By: Relevance
“…Males also had 6% more cortical white matter, similar to the 7.5% differences in older children (Reiss et al, 1996) but less than the 17-15% differences found in adults (Gur et al, 1999;Allen et al, 2003). Sexual dimorphism in head circumference has been observed as early as the second trimester in human and nonhuman primates on ultrasound (Joffe et al, 2005). Our study suggests that adult patterns of sexual dimorphisms of overall ICV and cortical gray matter volume are present at birth, whereas adult patterns of cortical white matter and lateral ventricle volumes develop after birth.…”
Section: Discussionmentioning
confidence: 61%
“…Males also had 6% more cortical white matter, similar to the 7.5% differences in older children (Reiss et al, 1996) but less than the 17-15% differences found in adults (Gur et al, 1999;Allen et al, 2003). Sexual dimorphism in head circumference has been observed as early as the second trimester in human and nonhuman primates on ultrasound (Joffe et al, 2005). Our study suggests that adult patterns of sexual dimorphisms of overall ICV and cortical gray matter volume are present at birth, whereas adult patterns of cortical white matter and lateral ventricle volumes develop after birth.…”
Section: Discussionmentioning
confidence: 61%
“…However, effects of fetal sex on prenatal bone geometry parameters, as presented in limb length (Fig. A and Table ), have not previously been identified in human or animal models . The maternal genome × fetal sex interaction on trabecular thickness (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest sexual dimorphism observed in life is that of head circumference, which was assessed by prenatal ultrasound as early as the second trimester of pregnancy (Joffe et al 2005). Although it is the least heritable, the cerebellum is the most sexually dimorphic brain structure.…”
Section: Sexual Dimorphism In Brain Developmentmentioning
confidence: 99%